The impact of financial globalization on economic growth in the Kurdistan region of Iraq: an empirical investigation / Ahmed Abdulrahman Khder Aga and Jwan Saeed Hussein - Abdulrahman Khder Aga, Ahmed; Hussein, Jwan Saeed (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This article delves into the linkage between Economic Growth and Financial Globalization within the Kurdistan context, utilizing yearly data spanning from 2007 to 2020 employing the Auto-Regressive-Distributed-Lag (ARDL) method. Empirical investigation revealed that there is a positive and significant linkage between Financial Globalization and economic growth in the case of Kurdistan in the long run over the 2007-2020; specifically, a 1% upturn in Financial Globalization was linked to an approximate 0.014% increase in GDP. Moreover, Oil Prices and Exchange Rate significantly and positively impacted economic growth in Kurdistan, suggesting that an increase in public revenue might result from an increase in oil price or changing of the exchange rate. Overall, the result implies that financial globalization, oil price, and exchange rate play significant roles in driving economic growth in Kurdistan.